The Influence of Brand Loyalty and Service Quality on Product Purchase Decisions at Bank Syariah Indonesia - Indah Kartika Sari; Marlina Widiyanti; Aslamia Rosa; Ahmad Maulana (Journal of Management Economic and Financial, 2024)
This research was conducted with the aim of determining the influence of brand loyalty and service quality on product purchase decisions at Bank Syariah Indonesia. The population in this study is all customers who purchase products at Bank Syariah Indonesia in the city of Palembang in 2023-2024. The sample used in this study was 100 respondents with a determination method using purposive sampling. The results of the multiple linear regression analysis show that brand loyalty and service quality have a positive and significant effect on product purchase decisions. In the brand loyalty variable, it is necessary to innovate the types of services and products offered. Where at this time, there are many conventional banks in Indonesia that offer attractive facilities and offers. In terms of service quality variables, it is hoped that Bank Syariah Indonesia can adjust to the number of employees.